Febrile illness in Asia: gaps in epidemiology, diagnosis, management for informing health policy - Shrestha, P; Roberts, T; Homsana, A; Myat, T; Crump, J; Lubell, Y; Newton, P (Elsevier, 2018)
There is increasing evidence on the aetiology and management of fevers in Asia, the importance of which has risen with declines in malaria incidence.To conduct a narrative review of the epidemiology and management of fevers in South and South-East Asia and to highlight gaps in our knowledge that impair evidence-based health policy decisions.A narrative review of papers published since 2012 of developments in fever epidemiology, diagnosis and treatment in South and South-East Asia. The papers that the authors felt were pivotal, from their personal perspectives, are discussed.We identified 100 studies. Among thirty studies (30%) including both children and adults that investigated three or more pathogens, dengue was reported the most frequently, by 15 (50%), followed by leptospirosis by 8 (27%), scrub typhus by 7 (23%) and Salmonella Typhi by 6 (20%). Among four studies investigating three or more pathogens in children, dengue and Staphylococcus aureus were the most frequent, followed by non-typhoidal Salmonella spp., Streptococcus pneumoniae, Salmomella Typhi, and scrub typhus. Increased awareness that rickettsial pathogens are common but will not respond to cephalosporins and that alternatives, such as tetracyclines, are required is needed.Many key gaps remain and consensus guidelines for study design are needed to aid comparative understanding of the epidemiology of fevers. More investment in developing accurate and affordable diagnostic tests for rural Asia and independent evaluation of those on the market are needed. Treatment algorithms, including simple biomarker assays, appropriate for empirical therapy of fevers in different areas of rural Asia should be a major aim of fever research. Enhanced antimicrobial resistance (AMR) surveillance and openly accessible databases of geography-specific AMR data would inform empirical and specific therapy policy. More investment in innovative strategies facilitating infectious disease surveillance in remote rural communities would be an important component of poverty reduction and improving public health.